Final Weight, Carcass Percentage and Abdominal Fat of Broiler Chickens Given Combined Mengkudu Leaf Flour (Morinda citrifolia) and Papaya Leaf Flour (Carica papaya) - Damaryanto Widharto Widharto; Ardian Ozzy Wianto (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2022)
The purpose of this study was to know of effect of substitution commercial feed with mengkudu (Morinda citrifolia L) leaf flour and pepaya (Carica papaya L) leaf flour combination in broiler chickens. The research use 60 day old chick of broilers which were devided into 4 treatments, that is T0 were given commercial feed without substitution, T1 were given commercial feed with substitution of Morinda citrifolia L. (1.5%) and Carica papaya L. (0.5%), T2 were given commercial feed with substitution of Morinda citrifolia L. (1.0%) and Carica papaya L. (1.0%) and T3 were given commercial feed with substitution of Morinda citrifolia L. (0.5%) and Carica papaya L. (1.5%). The variables observed final weight, carcasse percentage and abdominale fat percentage. The result of the study obtained that the final weight was 1286.67 (T0), 1398.00 (T1), 1361.33 (T2) and 1465.33 (T3), carcasse percentage 67.67 (T0), 69.58 (T1), 70.28 (T2) dan 69.24% (T3), and abdominale fat percentage 1.89 (T0), 2.00 (T1), 2.09 (T2) dan 1.95% (T3). The result of the analysis show an non significant in final weight, carcasse percentage and abdominale fat percentage. It could be concluded that substitution commercial feed with mengkudu (Morinda citrifolia L) and pepaya (Carica papaya L) leaf flour combination can’t increase of final weight, carcasse percentage and abdominale fat percentage in broiler chickens. Key word : commercial feed, mengkudu and pepaya leaves flour and economic analysis.